Educational Life-Forms - Cole, David R. author. aut Link
XIII, 134 p.
Keywords: This book takes the philosophy of Gilles Deleuze and applies it to educational practice. To understand how and why to do this, David R Cole puts forward the notion of educational life-forms in this writing, which are moving concepts based on Deleuzian principles. This book turns on and through the construction of the philosophy of life in education. The life-forms that will come about due to the philosophy of life in education rest on epiphanies, the virtual and affect. The author looks to infuse educational practice with the philosophy of life, though not through simple affirmation or a construction of counter metaphysics to representation in education. This book uses Deleuze for practical purposes and sets out to help teachers and students to think otherwise about the current praxis of education. "With this book Educational Life-Forms which is an examination of the significance of the philosophy of Gilles Deleuze for education, David R Cole proves himself to be one of the very small number of philosophers of education who has provided intelligent commentary of Deleuze's difficult corpus. Cole keenly appreciates the conceptual creativity of Deleuze especially in relation to the concepts of 'life forms' and 'body without organs' and effectively demonstrates its practical implications for education." - Michael A. Peters Professor, Educational Policy Studies, University of Illinois at Urbana-Champaign. “David R Cole's, Educational Life-Forms: Deleuzian Teaching and Learning Practice is a profound, speculative work that offers both new ways of thinking about the philosophy of Gilles Deleuze (as a practical thinker with ideas that can be applied at the 'coal face', as it were) and new ways of thinking about teaching and learning. It engages with actual policy debates as they are played out in the complex reality of the classroom situation and brings to them a fresh perspective developed through a close reading of Deleuze. This is an exciting new work which will berewarding reading for both Deleuzians and non-Deleuzians and is sure to win converts amongst the latter.” - Ian Buchanan, Editor Deleuze Studies Professor of Critical Studies, Dean of research in the Arts and Social Sciences University of Woolongong. In this thoughtful and engaging book, David R Cole has given us an answer to the important question of how Deleuze's philosophy enters into the practice of education. Cole situates this philosophy within existing debates around teaching and learning not only through a very lucid account of Deleuze's work and current theory, but also through highly effective and often moving examples of practice. This book is essential reading for anyone interested in Deleuze and education - James Williams Professor of European Philosophy, University of Dundee.